Determinants of piglet gut microbiome colonization: roles of genetics, nutrition, therapeutics, and the impact of enteric pathogens like PEDV - Lv, Yanzhuo; Zhou, Yu; Lu, Hongde; Dong, Hong; He, Zhiyuan (Frontiers in Cellular and Infection Microbiology, 2025)
The gut microbiota of piglets is crucial for intestinal health and immune function, yet highly susceptible to various factors. Multiple factors such as Genetic and Sow Factors, feeding environment, diet and pathogen combine to shape the gut microbiota of piglets. PEDV, a highly pathogenic and transmissible virus, disrupts the gut microbiota by damaging the intestinal epithelial barrier, leading to microbial imbalance, weakened gut immunity, and severe diarrhea. In this review, we systematically investigated the factors affecting microbial colonization in the gastrointestinal tract of piglets and the effects of PEDV infection on intestinal microecology, intestinal epithelial barrier and mucosal immunity. Meanwhile, the unique potential of Chinese herbal medicines compound represented by Qiwen Huangbai San in repairing the barrier, remodeling the flora and enhancing the immunity was discussed in depth. Through the above multidimensional perspectives, this review aims to provide a scientific basis and an effective preventive strategy for the construction of a comprehensive prevention and control program centered on Chinese herbs to alleviate the intestinal damage caused by PEDV in piglets.